Pancreatic neuroendocrine carcinoma with unique morphological features mimicking intraductal papillary mucinous carcinoma: A case report - Tanaka, Hidekazu; Minaga, Kosuke; Otsuka, Yasuo; Masuta, Yasuhiro; Kamata, Ken; Yamao, Kentaro; Takenaka, Mamoru; Hyodo, Tomoko; Kimura, Masatomo; Watanabe, Tomohiro; Kudo, Masatoshi (Frontiers in Medicine, 2022)
Background: Pancreatic neuroendocrine carcinoma (PanNEC) is a rare disease entity with rapid progression and poor prognosis. Here, we report a PanNEC case with unique morphological features mimicking intraductal papillary mucinous carcinoma. Case presentation: A 69-year-old Japanese man was referred to our hospital for further evaluation of weight loss and deterioration of diabetes mellitus. Contrast-enhanced computed tomography showed a solid and cystic mass with hypo-enhancement at the tail of the pancreas. The main pancreatic duct (MPD) was diffusely dilated without obstruction, accompanied by marked parenchymal atrophy. Multiple peritoneal and omental nodules were observed, suggesting tumor dissemination. Endoscopic retrograde cholangiopancreatography revealed that the mass correlated with the dilated MPD. During pancreatography, a large amount of mucus was extruded from the pancreatic orifice of the ampulla. Based on these imaging findings, intraductal papillary mucinous carcinoma was suspected. Per-oral pancreatoscopy (POPS)-guided tumor biopsies were conducted for the lesion's solid components. Histopathological examination of the biopsied material confirmed small-cell-type PanNEC with a Ki-67 labeling index of 90%. Due to his condition’s rapid decline, the patient was given the best supportive care and died 28 days after diagnosis. Conclusion: Although rare, PanNEC, which correlates with the MPD and is accompanied by marked dilation of the MPD, does exist as one phenotype. In such cases, POPS-guided biopsy could be a useful diagnostic modality.